Expression characteristics and biological significance of exosome-related genes in lung cancer - Qixiang Zhong; Yujie Zhao (Discover Oncology)
Abstract Background Lung cancer stands as one of the most prevalent malignancies globally, with its high morbidity and mortality intimately associated with its inconspicuous early symptoms, the advanced stages at diagnosis, and resistance to conventional therapeutic interventions. Exosomes, serving as pivotal mediators of intercellular communication, carry biomolecules that play crucial roles in tumorigenesis, progression, and metastasis, holding promise as novel targets for early diagnosis, prognostic evaluation, and treatment of lung cancer. Methods In this study, lung cancer-related datasets were obtained from the GEO database and TCGA. Through differential gene analysis, enrichment analysis, immune infiltration analysis, and drug regulatory analysis, exosome-associated genes pertinent to lung cancer were screened and identified. Results The research revealed significant downregulation of CRYAB, CAV1, HYAL1, and TUBB6 genes in lung cancer tissues, whereas SERINC2, PAICS, SLC2A1, and BIRC5 genes were markedly upregulated. These genes were predominantly enriched in biological processes such as cell migration, oxidative stress response, and cell cycle regulation, as well as in KEGG pathways like the IL-17 signaling pathway. Immune infiltration analysis demonstrated a high correlation between these genes and the infiltration levels of various immune cells. Furthermore, through drug-gene enrichment analysis and molecular docking experiments, significant correlations were found between drugs such as celecoxib and some exosome-related genes, with interaction targets existing between these drugs and CAV1, SLC2A1, and BIRC5 genes. Conclusion This study unveils the expression characteristics and biological significance of exosome-associated genes in lung cancer. The differential expression of these genes not only offers potential biomarkers for early diagnosis of lung cancer but also lays a foundation for further research into their biological functions in this disease.